Negosiasi Identitas Islam Lokal dan Citra Global pada Akun Youtube @Xyavieraputri - Febriyanti, Irfa Rizqia (UIN Sunan Ampel Surabaya, 2026)
This study is motivated by the growing prominence of digital spaces as arenas for negotiating local identity and global image. It aims to analyze the process of negotiating local identity and global image as represented through the YouTube content of @xyaviera. The research employs a qualitative approach using the semiotic analysis model developed by John Fiske, which operates across three levels of meaning reality, representation, and ideology to interpret visual, verbal, and symbolic signs in the uploaded videos, as well as to examine audience comments reflecting public reception of identity representation. The findings indicate that the hijab is presented as both a religious and cultural symbol that is adaptively negotiated within the global digital sphere. At the level of reality, the hijab and everyday practices represent local Islamic piety. At the level of representation, this identity is constructed through modern vlog aesthetics and global narratives. At the ideological level, the content constructs the meaning of a Muslim woman as modern, tolerant, and self-confident. Local identity is not erased; rather, it is transformed into a hybrid identity that gains international acceptance, as reflected in audience responses expressing both local pride and global appreciation. The study reveals that glocalization is not merely a process of adaptation but an active strategy to expand the meaning of identity within digital spaces. The novelty of this research lies in its in-depth analysis of the glocalization practices of Indonesian Muslim women’s digital identity through the YouTube platform, which has predominantly been examined within the contexts of Western economic and popular culture studies.